Finite-Time Impulsive Control of Financial Risk Dynamic System with Chaotic Characteristics - Li Ziyan; Tao Ke; Xia Qing; Xie Chengrong; Xu Yuhua (Complexity)
The control of financial risk has always been one of the important topics in financial research. Based on the theory of finance, this paper proposes a kind of financial risk dynamic system. By analyzing some properties of the dynamic system, the system shows obvious coexisting chaotic oscillations. In order to control the financial risk dynamic system effectively, this paper proposes a finite-time impulse controller to control the financial risk dynamic system. Simulation results show that the finite-time impulse controller has faster convergence speed than the impulse controller.